A comparison of IR- and UV-laser pretreatment to increase the bonding strength of adhesively joined aluminum/CFRP components. (May 2017) - Reitz, Valentina; Meinhard, Dieter; Ruck, Simon; Riegel, Harald; Knoblauch, Volker
Abstract: In this work different CFRP laminates (called "A" and "B") were pre-treated using IR- and UV-laser prior to adhesive bonding. The achieved surface conditions were characterized by optical methods and correlated with mechanical properties of adhesively bonded hybrid Al/CFRP single-lap joints. Two opposing effects could be detected on both CFRP laminates after IR-laser pre-treatment: strength increasing surface activation and reducing weakening of the fiber-matrix interface in near surface areas. However, using UV-radiation it was possible to activate the surface damage-free for A whereas B exhibited thermal induced damaging of the fiber-matrix adhesion comparable to IR laser treatment. Furthermore, it was shown that surface activation by laser pre-treatment strongly depends on the used CFRP laminate. IR- and UV-laser pre-treatment of A leads to a significant increase of shear strength, whereas for B even a slight reduction was observed compared to chemical cleaning with acetone which was the reference process.